Early Reciprocal Effects in a Murine Model of Traumatic Brain Injury and Femoral Fracture - Katharina Ritter; Kirsten Jung; Christopher Dolderer; Dominik Appel; Christine C. Oswald; Ulrike Ritz; Michael K. E. Schäfer (Hindawi Limited, 2021)
Traumatic brain injury (TBI) represents a major cause of death and disability in early adulthood. Concomitant extracranial injury such as long bone fracture was reported to exacerbate TBI pathology. However, early reciprocal effects and mechanisms have been barely investigated. To address this issue, C57BL/6N mice were subjected to either the controlled cortical impact (CCI) model of TBI, fracture of the left femur (FF), combined injury (CCI+FF), or sham procedure. Behavioral alterations were monitored until 5 days post injury (dpi), followed by (immuno-)histology, gene and protein expression analyses using quantitative PCR, western blot, and ELISA. We found that CCI+FF mice exhibited increased neurological impairments, reduced recovery, and altered anxiety-related behavior compared to single injury groups. At 5 dpi, cerebral lesion size was not affected by combined injury but exaggerated hippocampal substance loss and increased perilesional astrogliosis were observed in CCI+FF mice compared to isolated CCI. Bone gene expression of the osteogenic markers Runx2, osteocalcin, alkaline phosphatase, and bone sialoprotein was induced by fracture injury but attenuated by concomitant TBI. Plasma concentrations of the biomarkers osteopontin and progranulin were elevated in CCI+FF mice compared to other experimental groups. Taken together, using a murine model of TBI and femoral fracture, we report early reciprocal impairments of brain tissue maintenance, behavioral recovery, and bone repair gene expression. Increased circulating levels of the biomarkers osteopontin and progranulin indicate ongoing tissue inflammation and repair. Our results may have implications for future therapeutic approaches to interfere with the pathological crosstalk between TBI and concomitant bone fracture.